Sex ratio at Birth in a Tertiary Care Hospital in Western Nepal are the Trends Changing? - Aryal, Shreyashi; Kalakheti, Balkrishna (Journal of Nepal Paediatric Society, 2016)
Introduction: Sex ratio at birth remains unchanged in absence of human intervention. A tendency of skewing towards males is seen in Asian population attributable to various reasons, foremost being abortions. The decreasing number of female population is a form of gender discrimination and has serious implications for both sexes in the future. The purpose of this study was to analyze the trends of sex ratio at birth among deliveries at Lumbini Medical College Teaching Hospital, Palpa, Nepal over the past eight years. Materials and Methods: A retrospective audit of deliveries from 1st January 2008 to 31st December 2015 was carried out. Sex ratio at birth was calculated and its relationship with maternal age, birth order and number of previous abortions was analyzed. Results: The total number of live-births during the study period was 9394 consisting of 5008 male and 4350 female with an overall sex ratio at birth of 112.6. Every year, there was an increasing trend in total number of live births and sex ratio at birth. The number of male births increased with increase in parity but there was no statistical difference seen between maternal age, parity and number of abortions for male and female births. Conclusion: The sex ratio at birth in hospital deliveries is unbalanced with inclination towards male, more so in women with high parity. Additional research exploring the reason for increase in male births is needed, so that potential programs which can reverse this trend can be implemented. J Nepal Paediatr Soc 2016;36(1):68-71